First report of Veronaea botryosa as a causal agent of chromomycosis in frogs. (2nd April 2015) - Hosoya, Tsuyoshi; Hanafusa, Yasuko; Kudo, Tomoo; Tamukai, Kenichi; Une, Yumi
Abstract : A dematiaceous hyphomycete, isolated from frogs, was determined as the possible etiologic agent of a case of systemic chromomycosis this cold-blooded animal. The fungus was identified as Veronaea botryosa on the basis of morphological features observed in histopathological examination and molecular phylogenetic evidence. Although V. botryosa is known to be distributed widely in litter and as a human pathogen, this is the first confirmed report of its involvement in a lethal infection in a cold-blooded animal, including an anuran.